Chloride-induced corrosion on reinforcing steel: from the fundamentals to the monitoring techniques - Montemor, M. F. (2021)
One of the most important causes for reinforcing steel corrosion is the presence of chloride ions. They cause localised breakdown of the passive film that initially forms on steel as a result of the alkaline nature of the pore solution in concrete. The harmful chloride ions can be originated from the use of contaminated mix constituents or from the surrounding environment. The determination of a critical level, above which serious problems can occur, has been one of the main goals of investigation. Unfortunately, it is difficult to establish such a value since the chloride level is influenced by several factors. Thus, after concrete contamination, it is of fundamental importance to follow the activity of chlorides and the state of the reinforcing rebars. In this respect, the use of electrochemical techniques such as polarisation resistance, electrochemical impedance, galvanostatic pulse and potential measurements have shown to be powerful tools. Nevertheless, the interpretation of the results becomes sometimes a difficult task. A large number of authors have dedicated several studies to the interpretation of such measurements and a highly dispersed number of interpretations can be found in literature. The aim of this paper is to present an overview on the state-of-the-art of the most important aspects of the corrosion process initiated by chlorides, its development and monitoring techniques.